Relationship between front-of-pack labeling and nutritional characteristics of food products: An attempt of an analytical approach - Martini, Daniela; Marangoni, Franca; Banterle, Alessandro; Donini, Lorenzo Maria; Riccardi, Gabriele; Poli, Andrea; Pellegrini, Nicoletta (Frontiers in Nutrition, 2022)
The adoption of supplementary nutrition information, i.e., front-of-pack labelling (FOPL), on pre-packed food products is advocated as a tool to improve the consumers’ knowledge of the nutrient content or the nutritional quality of foods, but also to drive products reformulation by the food industry. Ultimately, FOPL should help people to select foods in order to compose an overall balanced diet, which is essential for health. However, the extent to which the different FOPL systems proposed in the European Union (EU) (interpretative or informative) are effectively able to convey the information useful to improve both food choices and dietary habits of the consumers is still under debate and needs to be analyzed in detail. The use of 3 FOPL schemes proposed within the EU (Nutri-Score, Keyhole and NutrInform Battery) to compare products available on the Italian market within different food categories, highlights some critical issues: 1) different FOPL provide to consumers different kinds of information; 2) systems based on similar theoretical approaches can provide conflicting information; 3) the algorithms on which interpretative FOPL are based can give the same summary information for products differing in nutrient composition, impact on the overall dietary balance and therefore on the health of people with different characteristics, physiological/pathological conditions, and nutritional requirements; 4) on the other hand, products with similar nutrient composition can obtain different interpretative FOPL; 5) informative systems are generally more complex and require greater both attention and knowledge from the consumer; 6) FOPL based on 100 g of product overlook the role of portion (and frequency of consumption) in determining the nutrient intake without informing on the contribution of a single food to the overall diet; 7) FOPL based on scoring systems could promote the reformulation of selected products, especially with a composition very close to the threshold limits; 8) for the portion-based informative FOPL systems, the incentive for reformulation could essentially involve the reduction of portion size. Finally, the importance of nutritional education interventions, which are required to encourage the use by consumers of informative FOPL systems, cannot be neglected to improve the quality of diets regardless of the FOPL used.